TEOLOGI PUBLIK DAN BUDAYA HUMAT TIMOR: RELEVANSINYA BAGI MULTIKULTURALISME DI INDONESIA - Rikhardus Poli; Raymundus I Made Sudhiarsa (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2025)
This paper focuses on the relevance of the humat culture (brotherhood) in the Timorese tradition of East Nusa Tenggara (NTT) as a foundation for developing a contextual public theology within Indonesia’s multicultural society. In the Timorese tradition, humat is understood as brotherhood and solidarity that transcend biological ties, manifested through practices of mutual cooperation (gotong royong), customary reconciliation, and openness toward “the other.” Using a qualitative method, particularly a descriptive-analytical approach, this study reveals that humat embodies three essential dimensions aligned with the principles of public theology: solidarity, inter-identity brotherhood, and reconciliation. These dimensions contribute significantly to strengthening Indonesian multiculturalism amid the threats of intolerance and social fragmentation. The purpose of this paper is to demonstrate that humat culture can serve as a public ethic that encourages the Church, religious communities, civil society, and the state to build an inclusive, just, and peaceful common life. Thus, the findings affirm that humat is not merely a local cultural heritage of Timor, but an ethical-theological source of inspiration for developing a relevant public theology in Indonesia’s multicultural context.